2007
DOI: 10.1007/s10494-007-9092-4
|View full text |Cite
|
Sign up to set email alerts
|

Initial Conditions and Near-Field Dynamics in Turbulent Liquid Sheets

Abstract: High-speed liquid "curtains" have been proposed to protect solid structures in fusion energy applications. Minimizing free-surface waves and spray formation in such flows is important for effective protection in this application. In this work, free-surface waves and turbulent breakup were studied experimentally in jets of water issuing from a rectangular nozzle into ambient air at a Reynolds number of 1.2×10 5 . Laser-Doppler anemometry was used to characterize the streamwise and transverse velocity components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…It also suggests that velocity profile relaxation is relatively weak in turbulent jets as the 1 term is always essentially much larger than δ 0 /d 0 . This conclusion is consistent with the experiments of Durbin et al [31], who found that having a thin boundary layer is less important than having low turbulence for reducing jet breakup. Additionally, the overall production-dissipation ratio is controlled by more than the boundary layer thickness (or equivalently, the velocity profile), as will be discussed in the next sections.…”
Section: Shear Instability Paradoxsupporting
confidence: 92%
See 1 more Smart Citation
“…It also suggests that velocity profile relaxation is relatively weak in turbulent jets as the 1 term is always essentially much larger than δ 0 /d 0 . This conclusion is consistent with the experiments of Durbin et al [31], who found that having a thin boundary layer is less important than having low turbulence for reducing jet breakup. Additionally, the overall production-dissipation ratio is controlled by more than the boundary layer thickness (or equivalently, the velocity profile), as will be discussed in the next sections.…”
Section: Shear Instability Paradoxsupporting
confidence: 92%
“…This has not been recognized in the turbulent jet breakup literature, but it is consistent with the experiments of Durbin et al [31]. Durbin et al compared the breakup of turbulent liquid (sheet) jets produced by nozzles with and without a screen placed immediately upstream.…”
Section: The Effect Of the Integral Scale On Velocity Profile Relaxationsupporting
confidence: 80%